2008
DOI: 10.1590/s0085-56262008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Comunidade de Syrphidae (Diptera): diversidade e preferências florais no Cinturão Verde (Santa Cruz do Sul, RS, Brasil)

Abstract: Syrphidae (Diptera) community: diversity and floral preferences in the Green Belt (Santa Cruz do Sul, RS, Brazil). The aim of this study was to investigate the Syrphidae community in the area of the Green Belt of Santa Cruz do Sul, RS, Brazil, as well as to obtain information on the structure and composition of this community, its floral preferences and the interactions between the species in the food resource utilization. The specimens were collected with entomological net, from September/2001 to January/200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
(17 reference statements)
0
10
2
Order By: Relevance
“…According to Namaghi & Husseini (2009) and Marcos-García et al . (2012), the collecting method can influence the diversity and richness of species obtained, and this might explain the large difference between our results and the results of Morales & Köhler (2006, 2008). The latter authors used a manual collecting method, and the 2006 study was specifically directed at obtaining flies from Eryngium horridum Malme (Apiaceae).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…According to Namaghi & Husseini (2009) and Marcos-García et al . (2012), the collecting method can influence the diversity and richness of species obtained, and this might explain the large difference between our results and the results of Morales & Köhler (2006, 2008). The latter authors used a manual collecting method, and the 2006 study was specifically directed at obtaining flies from Eryngium horridum Malme (Apiaceae).…”
Section: Discussioncontrasting
confidence: 93%
“…The species richness found in this study is less than that found by Morales & Köhler (2006, 2008), Marinoni et al (2004, 2006), Jorge et al . (2007), and de Souza et al .…”
Section: Discussioncontrasting
confidence: 89%
“…The morphology of flowers of the Apiaceae is compatible with the short mouthparts of adult Syrphidae hoverflies, thus facilitating access to nectar and pollen (Morales and Köhler, 2008). Flowers of the Asteraceae, including marigold species, are also attractive to syrphids, as verified by Robertson (1929), who reported that 25% of the 257 species of this family serve as hosts for hoverflies, and by Sajjad and Saeed (2010) who established that the Asteraceae is one of the families most visited by Syrphidae.…”
Section: Erysimimentioning
confidence: 84%
“…Syrphidae larvae are known as important natural enemies of aphids in different crops (Oliveira et al, 2003;Ghahari et al, 2008), including greenhouses (Pimentel, 2007), due to their capacity of consuming great amounts of insects during its developmental time (Marinoni et al, 2007). Furthermore, adults perform an important role as pollinators of different vegetable species (Morales and Köhler, 2008). Thus, further studies such as those related to T. duplicatus biology and also multiplication techniques are necessary to investigate the possibility of using this predator as a biological control agent for both M. ochroloma and M. semilaevis larvae in different Brassicaceae crops.…”
Section: Resultsmentioning
confidence: 99%